A nano heterostructure with step-accelerated system toward optimized photocatalytic hydrogen evolution. (8th January 2022) - Fang, Hao; Wu, Bo; Sheng, Xiaoli; Wang, Yanyun; Bu, Xiaohai; Zhou, Yuming; Dong, Guomeng; Yang, Chenghan; Zhang, Xian
Abstract: Adequate light absorption and high carrier separation/transfer efficiency are central to elevate the development of highly efficient photocatalytic hydrogen evolution. Herein, a unique nano heterostructure is constructed by translocating 0D CdSe@(Zn, Cd)Se@ZnS quantum dots (CSS QDs) into the 3D hollow spherical graphite carbon nitride (SCN). The ultrafast TA spectroscopy and electrochemical measurements were measured to reveal the enhanced surface dependent electron transfer efficiency. Besides, the density functional theory (DFT) calculations further explained the mechanism of electrons transfer between interfaces. As expected, benefiting from the structural advantages of SCN and the channel-driven effectiveness produced by a step-accelerated system which is composed of (Zn, Cd)Se and ZnS double-shell layers of CSS QDs, the optimal hydrogen evolution rate of the prepared material in the photocatalytic hydrogen evolution reaction reached 132.5 μmol h −1, which was 7.6 times higher than that of the pure SCN under visible light irradiation. This work provides a novel avenue into the construction of nano heterostructure for solar hydrogen evolution. Highlights: CdSe@(Zn, Cd)Se@ZnS QDs/SCN nano heterostructures were prepared. The existence of CdSe QDs achieved wide absorption and strong photoreaction. The double shells of QDs consist of the step-accelerated system. The step-accelerated system accelerates the charge separation and transfer. Analysis of the path of electronic transfer and hydrogen evolution mechanism.